The Effect of Tree Planting Counseling on Building Environmental Awareness Character in Private Schools - Sibuea, Alya Az Zahra; Nanda, Meutia; Rahmada, Lily; Zaki, Ahmad; Zahra, Nurul (Universitas Ibn Khaldun Bogor, 2025)
Air pollution is a global issue that threatens health and ecosystems. Tree planting is an effective solution because it can absorb carbon dioxide, produce oxygen, and filter air pollutants. This study was conducted to determine the extent of the influence of tree planting counseling in building the character of environmental care in schools. The method in this study uses quantitative with a one group pre-test post-test design approach. The sample size in the study amounted to 42 respondents using the total sampling formula. Data analysis was carried out using the shapiro-wilk test to check whether a sample of data came from a normal distribution. After that, use the paired sample t-test if the data is normally distributed and the Wilcoxon test if the data is not normally distributed. Based on the results of the study, the pre-test average value of 8.19 with a minimum value of 6.00 increased to a post-test average of 19.05 with a minimum value of 17.00 and a maximum of 20.00. The p-value of 0.000 <0.05 indicates that there is a significant difference between before and after counseling, so it can be concluded that counseling has a positive effect on increasing students' environmental care character. This indicates that the counseling is effective in increasing students' understanding of the importance of tree planting as part of building the character of environmental care.